PROCESSAMENTO E CARACTERIZAÇÃO DE MISTURAS DE PEBD VIRGEM E RECICLADO COM BORRACHA DE PNEU DESVULCANIZADA POR MICROONDAS “IN SITU”. - Vieira Filho, Armando Madalosso (2009)
Finding new ways and techniques of recycling has been one of the main paths searched by investigators to solve the problem of the garbage. For this study were chosen two of the polymers with large volumes of post-consumer material: LDPE and rubber tire. Several studies have been made to incorporate rubber tire in polymers by following different paths one of them is the devulcanization of rubber tire by microwave. The focus of this study was process and characterize blends of virgin and / or recycled LDPE with ground tire rubber. Both formulations, virgin and recycled LDPE, were made with percentage by weight of 0, 5, 10, 20 and 40 of rubber in and with percentage by weight of 0 and 10 in the blends of 50% virgin / 50% recycled LDPE. The formulations were processed into a of single screw extruder, granulated, injected and treated with microwave “in situ”. Tests were made for size distribution of the rubber, tensile, bending, optical and scanning electron microscopy, DSC and infrared spectroscopy. As results obtained were: a rubber tire can be used as an additive for staining, mechanical properties similar to almost all formulations was obtained with up to 10% of tire rubber. The amount of rubber incorporated and composition (recycled or virgin) influence the mechanical and thermal properties of some blends. The treatment with microwaves "in situ" presented influence on the mechanical and thermal properties in the formulations tested, presenting differential properties, such as increased maximum stress in some formulations, demonstrating that the study of the treatment is technologically interesting.